Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Evaluate the limit $\lim_{x\to 0} (\frac{\sqrt{x^2+1}-1}{(\sqrt{x^2+16}-4})$ I know the limit is 4 by looking at the graph of the function, but how can I algebraically show that that is the limit?

share|improve this question

2 Answers 2

Just multiply the numerator and the denominator by $$(\sqrt{x^2+1}+1)(\sqrt{x^2+16}+4)$$ to get

$$\frac{\sqrt{x^2+1}-1}{\sqrt{x^2+16}-4}$$ $$=\frac{(\sqrt{x^2+1}-1)(\sqrt{x^2+1}+1)}{(\sqrt{x^2+16}-4)(\sqrt{x^2+16}+4)}\cdot\frac{\sqrt{x^2+16}+4}{\sqrt{x^2+1}+1}$$


and cancel out $x^2$ as $x\ne0$ as $x\to0$

share|improve this answer

Or$$\lim_{x\to 0} (\frac{\sqrt{x^2+1}-1}{(\sqrt{x^2+16}-4})=\lim_{x\to 0} \frac{\sqrt{x^2+1}-1}{x^2}\cdot\lim_{x\to 0} \frac{(\frac{x}{4})^2}{\sqrt{(\frac{x}{4})^2+1}-1}\cdot4= \frac{1}{2}\cdot2\cdot4=4$$

We applied $$\lim_{t\to 0}\frac{(1+t)^r-1}{t} =r$$

share|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.